2004
DOI: 10.1002/cncr.20271
|View full text |Cite
|
Sign up to set email alerts
|

The association between 3‐hydroxy‐3‐methylglutaryl conenzyme A inhibitor use and breast carcinoma risk among postmenopausal women

Abstract: BACKGROUNDStatin use has increased dramatically in the U.S. in the past decade. Animal and mechanistic studies suggested that statins may have an inhibitory effect on cancer proliferation, including breast carcinoma. However, statins have been found to be carcinogenic in rodents and one clinical trial found an excess of breast carcinoma cases in the treatment group.METHODSThe current study assessed whether the use of statins altered the risk of breast carcinoma in older women. The population‐based, case–contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
1
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 47 publications
4
79
1
1
Order By: Relevance
“…A large case-control study from the General Practice Research Database, an automated database containing drug prescription and medical information on more than three million people in the United Kingdom, found no association between current statin use and breast cancer risk [10]. Interestingly, another large case-control study with cases from a population-based tumor registry reported no overall association of statins with breast cancer incidence but did find that women who had used statins for more than five years had an approximately 30% lower breast cancer incidence than never users [4]. Two other case-control studies observed no association between statin use and breast cancer risk [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large case-control study from the General Practice Research Database, an automated database containing drug prescription and medical information on more than three million people in the United Kingdom, found no association between current statin use and breast cancer risk [10]. Interestingly, another large case-control study with cases from a population-based tumor registry reported no overall association of statins with breast cancer incidence but did find that women who had used statins for more than five years had an approximately 30% lower breast cancer incidence than never users [4]. Two other case-control studies observed no association between statin use and breast cancer risk [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…For example, laboratory studies have shown that lipophilic statins such as simvastatin and fluvastatin inhibit mammary tumor growth by approximately 50% at doses equivalent to those used in humans for reducing cholesterol [2]. Thus far, observational studies of the association between statins and risk of developing breast cancer have yielded mixed results, with the majority finding no association [3][4][5][6][7][8][9][10]. To our knowledge, no studies have examined statin use and breast cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic pharmacy database allowed for precise calculation of total exposure to statins; the duration of statin use was accurately reflected in the number of prescriptions dispensed, as few Kaiser patients fill prescriptions outside the Kaiser formulary system. This produces a (17,18,(32)(33)(34)(35). Only two studies have investigated the effect of statins on specific histologic type.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of these large cohort studies by Cauley et al found that statin use was associated with an 18% lower risk of breast cancer when statin use was limited to hydrophobic statin users among women enrolled in the Women's Health Initiative (21). Other observational studies have reported sometimes large reductions in the risk of breast cancer (30-72%) associated with use of statins (16,18,20). Cauley et al also report no association between statin use and breast cancer risk among users of estrogen plus progestin or among never/past hormone therapy user but a nonstatistically significant reduced risk (22%) among users of estrogen alone.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies that report on statin use and breast cancer risk are varied and report no effect on risk and both increases and decreases in risk (13)(14)(15)(16)(17)(18)(19)(20)(21). To assess the association between statin use and breast cancer risk, we conducted a cohort study within a large integrated health care delivery system that contains computerized information on medication use, incident cancers, and risk factors for breast cancer.…”
Section: Introductionmentioning
confidence: 99%